PSI-20 portfolio efficiency analysis with SFA - Ferreira, N. B. (2015)
The determination of the study was to assess the technical efficiency of the individual companies and their respective groups of the Portuguese stock market. In order to achieve that were combined the input variables “market value and return” with exogenous variables such as “interest income," “depreciation," “cost of goods," “employees” and “net sales” in a Stochastic Frontier Analysis model. The technical efficiency of the PSI-20 enterprises index was estimated discovering the factors which assurance to efficiency variability, applying the SFA approach main improvement which lies in its potential to categorize between measurement error and systematic inefficiencies in the estimation process. The results revealed that the technical efficiency is higher for the enterprises in industry, construction and distribution economic sectors whereas the commercial banking sector has the lowest technical efficiency scores. The “employees” and “depreciation” variables are the elements that most enhance to the stock market inefficiency.